Obieg apokryfów Starego Testamentu w literaturze koptyjskiej - Piwowarczyk, Przemysław (The Biblical Annals, 2024)
The article surveys the Old Testament Apocrypha in Coptic literature. After problematizing the nature and list of Apocrypha, specifically in the Egyptian context, it pragmatically uses Clavis apocryphorum Veteris Testamenti as a reference point. The analytic part shows that MSS containing Apocrypha constitute the very margin of the Coptic literary production. Such texts were relatively popular until the fifth century CE, but their popularity waned, and only some selected motifs were reworked in new compositions, mainly of homiletical nature. Moreover, the analysis of extant library catalogues and book lists on papyri, ostraca, and inscriptions proves the almost complete absence of Apocrypha, at least among the monastic readings. The interpretative part underlines the rise of the monasticization of Coptic Christianity and the tightening of episcopal control as crucial factors in the decline of apocryphal production.